Research and implementation of college students full information inquiry common information model - Tian-ping LAI; Su-mei WANG; Yi-ming PENG; Miao SHEN; Zhi-tong GAO (Tongxin xuebao)
Information query common information model plays important role in college student integrated data query.Proposed a common information model of full information query.Based on an analysis of actual demand,proposed structure of the data and card data two concepts.Through in-depth needs analysis,summarized five basic elements :data entry model,data views,user roles,permissions management and root permissions.Elaborate model implementation in view of the establishment for the data source integration,data entry and other key issues .Practice shows that the model has a high degree of adaptation and practicality.Basically solve the issues such as data entry permissions,roles classified staff,administrative-level permissions,a variety of data sources.